Ligand exchange processes on solvated zinc cations - DFT analysis of hydrogen cyanide exchange on [Zn(HCN)6]2+ - Alzoubi, Basam; Puchta, Ralph; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2009)
The mechanisms for hydrogen cyanide exchange on [Zn(HCN)6] 2+ were studied using density functional theory (B3LYP/6311+G), and showed that the limiting dissociative (D) pathway is more favorable than the associative interchange (Ia) mechanism. The activation barrier for the dissociative mechanism (7 kcal-mol-1) is clearly lower than for the interchange mechanism (15.9 kcal-mol-1). © 2009 WILEYVCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Coordination chemistry; Coordination modes; Density functional calculations; Hcn exchange; Zinc